Application of ultraviolet light-emitting diodes (UV-LED) to full-scale drinking-water disinfection - Jarvis, Peter; Autin, Olivier; Goslan, Emma H.; Hassard, Francis (MDPI, 2019)
Ultraviolet light-emitting diodes (UV-LEDs) have recently emerged as a viable technology for water disinfection. However, the performance of the technology in full-scale drinking-water treatment systems remains poorly characterised. Furthermore, current UV disinfection standards and protocols have been developed specifically for conventional mercury UV systems and so do not necessarily provide an accurate indication of UV-LED disinfection performance. Hence, this study aimed to test the hypothesis that a full-scale UV-LED reactor can match the Cryptosporidium inactivation efficiency of conventional mercury UV reactors. Male-specific bacteriophage (MS2) was used as the Cryptosporidium spp. surrogate microorganism. The time-based inactivation efficiency of the full-scale reactor was firstly compared to that of a bench-scale (batch-type) UV-LED reactor. This was then related to mercury UV reactors by comparing the fluence-based efficiency of the bench-scale reactor to the USEPA 90% prediction interval range of expected MS2 inactivation using mercury UV lamps. The results showed that the full-scale UV-LED reactor was at least as effective as conventional mercury UV reactors at the water-quality and drive-current conditions considered. Nevertheless, comparisons between the bench- and full-scale UV-LED reactors indicated that improvements in the hydraulic flow profile and power output of the full-scale reactor could help to further improve the efficiency of UV-LED reactors for municipal drinking water disinfection. This represents the world’s first full-scale UV-LED reactor that can be applied at municipal water treatment works for disinfection of pathogenic microorganisms from drinking water.
Keywords: disinfection; Cryptosporidium; bacteriophage; chemical actinometry; drinking water; UV-LED